1978
DOI: 10.1002/bip.1978.360170815
|View full text |Cite
|
Sign up to set email alerts
|

Tail‐fiber attachement in bacteriophage T4D studied by quasielastic light scattering–band electrophoresis

Abstract: SynopsisMixtures of bacteriophage T4D particles with up to six tail fibers attached were separated and analyzed in a quasielastic light scattering-band electrophoresis apparatus. The electrophoretic mobilities and diffusion coefficients of the separated bands were determined during the same experiment. Species differing in mobility by 0.05 X lov4 cm*/V sec were resolved. Henry's electrophoresis theory for spheres indicates that each tail fiber contributes about 240 effective positive charges to the phage struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1979
1979
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…The addition of the first and second tailfibres causes a larger relative increase in rotational friction than in translational friction. Using the technique of quasielastic light-scattering-band electrophoresis developed by Lim et al (1977), Baran & Bloomfield (1978) have obtained results for the/ t 's that are in excellent agreement with the theoretical predictions. No results are yet available for rotation.…”
Section: -73 300supporting
confidence: 54%
See 1 more Smart Citation
“…The addition of the first and second tailfibres causes a larger relative increase in rotational friction than in translational friction. Using the technique of quasielastic light-scattering-band electrophoresis developed by Lim et al (1977), Baran & Bloomfield (1978) have obtained results for the/ t 's that are in excellent agreement with the theoretical predictions. No results are yet available for rotation.…”
Section: -73 300supporting
confidence: 54%
“…al. 1977;Baran & Bloomfield, 1978;Welch & Bloomfield, 1978). The values of D t used to extract the R h 's are corrected for rotational effects (Wilson & Bloomfield, 19796;Hopman & Koopmans, 1979).…”
Section: T-evenbacteriophagementioning
confidence: 99%
“…The bacteriophage head presents a net negative charge, while the tail fibers present a net positive charge 77 . Thus, the dipole moment of a phage particle causes the head to be oriented towards a positively charged surface 78 .…”
Section: Oriented Immobilizationmentioning
confidence: 99%
“…It was reported that the net charge of most viruses is negative [67,68]. In the work of Baran, we know that the tail fibers of T4 bacteriophages are highly positively charged and the head structures are negatively charged, implying that the tail fibers can be electrostatically attracted to the negatively charged membrane surface of their targets for further proliferation inside the bacteria cells [69]. Anany et al had determined the overall charge of one mutant of T4 bacteriophage composed of head and tail fibers as −5.31 ± 0.67 mV, whereas the charge was detected as 1.80 ± 0.19 mV for another mutant with only tail and tail fibers [70].…”
Section: Electric Depositionmentioning
confidence: 99%